The impact of organizational culture on project management in matrix organizations - J. M. Morrison; C. J. Brown; E. V.D.M. Smit (South African Journal of Business Management, 2008)
This research empirically examined the relationship between organizational culture and the effectiveness of project management. The study made use of two conceptually developed constructs. The one, a framework of organizational culture, consists of twelve dimensions that emerged from a study of the project management literature as important organizational conditions for effective project management. The second construct, project management effectiveness, comprises eleven dimensions constituting the persistent leading and outcome indicators of project management success, similarly based on literature. The research found a statistically significant relationship between the two constructs in a sample of matrix organizations. Each of the twelve dimensions of organizational culture also correlated significantly with project management effectiveness. A total of 29 organizations, operating within the boundaries of South Africa, took part. Although generalizability is not possible, given the sample size, the study nevertheless takes a substantial step forward in this important context of project management. Pointers are offered for future research, and for organizations that find that project management fails to perform in accordance with their expectations.
Keywords: 650